Surge capacity of intensive care units in case of acute increase in demand caused by COVID‐19 in Australia. Issue 10 (19th April 2020) - Litton, Edward; Bucci, Tamara; Chavan, Shaila; Ho, Yvonne Y; Holley, Anthony; Howard, Gretta; Huckson, Sue; Kwong, Philomena; Millar, Johnny; Nguyen, Nhi; Secombe, Paul; Ziegenfuss, Marc; et al.
Abstract: Objectives: To assess the capacity of intensive care units (ICUs) in Australia to respond to the expected increase in demand associated with COVID‐19. Design: Analysis of Australian and New Zealand Intensive Care Society (ANZICS) registry data, supplemented by an ICU surge capability survey and veterinary facilities survey (both March 2020). Settings: All Australian ICUs and veterinary facilities. Main outcome measures: Baseline numbers of ICU beds, ventilators, dialysis machines, extracorporeal membrane oxygenation machines, intravenous infusion pumps, and staff (senior medical staff, registered nurses); incremental capability to increase capacity (surge) by increasing ICU bed numbers; ventilator‐to‐bed ratios; number of ventilators in veterinary facilities. Results: The 191 ICUs in Australia provide 2378 intensive care beds during baseline activity (9.3 ICU beds per 100 000 population). Of the 175 ICUs that responded to the surge survey (with 2228 intensive care beds), a maximal surge would add an additional 4258 intensive care beds (191% increase) and 2631 invasive ventilators (120% increase). This surge would require additional staffing of as many as 4092 senior doctors (245% increase over baseline) and 42 720 registered ICU nurses (269% increase over baseline). An additional 188 ventilators are available in veterinary facilities, including 179 human model ventilators. Conclusions: The directors of Australian ICUs report that intensive care bed capacity could be near tripled in response to the expected increase in demand caused by COVID‐19. But maximal surge in bed numbers could be hampered by a shortfall in invasive ventilators and would also require a large increase in clinician and nursing staff numbers.